The Digital Transformation of Crisis Management: Visions of the Future - Struijk, Mylene; van der Varst, Laurens (Proceedings of the International ISCRAM Conference, 2026)
Digital technologies have a transformational impact on society, organizations, and individuals. Crisis management is not immune to such transformational changes either. However, digital transformation of crisis management is still in its early stages and often occurs within the boundaries of individual institutions and organizations. Current research and practical work on the topic tend to emphasize the role of digital technologies for specific crisis management processes and tasks, rather than envisioning what the outcomes of such a transformation might entail for crisis management as a discipline or, in other words, what ‘being digital’ means in a crisis management context. Hence, in this study, we identify different visions of the future through a series of semi-structured interviews with crisis professionals in The Netherlands. Importantly, we tease out three tension spaces among such alternative visions that open up a range of questions that warrant attention today. By engaging with divergent visions of the future and the questions they raise, we can identify novel concepts, concerns, and implications we may face and that require proactive action today.